Changes in the content of Puerarin-PLGA nanoparticles in mice under the influence of alcohol and analysis of their antialcoholism - Siyu Qiang; Lixiang Gu; Yu Kuang; Minyao Zhao; Yu You; Qin Han (Journal of Applied Biomaterials & Functional Materials, 2023)
To observe the metabolic changes and antialcoholic effect of Puerarin-PLGA nanoparticles (PUE-NP) in mice. PUE-NP was prepared and characterized by particle size distribution and morphology. The mouse models with acute alcoholism were established to observe their behavioral changes after alcohol poisoning. The expressions of biologically active enzymes such as CRE, BUN, AST, ALT in serum and SOD and TLR4 in liver of mice in each group were detected, and the pathological changes in liver and kidney tissues were observed by HE staining. The PUE-NP metabolism in mice was determined by in vitro release assay and HPLC. PUE-NP nanoparticles had good morphology and structure, and the mouse models with alcohol poisoning were established successfully. Compared with alcohol group, puerarin and PUE-NP increased the disappearance latency time of righting reflex, and the recovery time of righting reflex was significantly shortened. Water maze results showed that Puerarin and PUE-NP had inhibitory effect on impaired memory. HPLC results showed that PUE-NP reached its peak in mice after 1 h, and the content percentage was twice that of puerarin preparation alone, and the distribution time of puerarin concentration in vivo was prolonged, indicating that PLGA nanoparticles had a loading and slow-release effect on puerarin and increased the bioavailability of puerarin in mice. In addition, compared with the alcohol group, Puerarin and PUE-NP improved serum ALT, AST, CRE, and BUN levels in mice, enhanced SOD activity in liver, and inhibited TLR4 expression. The effect was better in the PUE-NP group than in the Puerarin group. PUE-NP delayed the release and metabolism of Puerarin and had better effect in the treatment of the alcoholic liver and kidney injury.